Lipidomic‐based investigation into the therapeutic effects of polyene phosphatidylcholine and Babao Dan on rats with non‐alcoholic fatty liver disease. (23rd November 2021) - Zhang, Yicong; Lv, Jinxiao; Zhang, Jiayuan; Lv, Zhihua; Yu, Mingming
Abstract: In recent years, with the improvement of people's living standards, non‐alcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease in the world. In this paper, the metabolic disorders in Sprague Dawley (SD) rats were induced by a choline‐deficient, l ‐amino acid–defined (CDAA) diet. The therapeutic effects of polyene phosphatidylcholine (PPC) and Babao Dan (BBD) on NAFLD were observed. Lipidomic analysis was performed using ultra‐high‐performance liquid chromatography‐Orbitrap MS, and data analysis and lipid identification were performed using the software LipidSearch. Both PPC and BBD can reduce lipid accumulation in the liver and improve abnormal biochemical indicators in rats, including reduction of triglycerides, total cholesterol, alanine transaminase and aspartate transaminase in serum. In addition, lipids in rat serum were systematically analyzed by lipidomics. The lipidomic results showed that the most obvious lipids with abnormal metabolism in CDAA diet–induced rats were glycerides (triglycerides and diacylglycerols), phospholipids and cholesterol esters. Both BBD and PPC partly reversed the disturbance to lipids induced by the CDAA diet. PPC may be more effective than BBD in alleviating NAFLD because it has a better effect on inhibiting the abnormal accumulation of lipids and reducing the inflammatory reaction in the body.